2016
DOI: 10.4084/mjhid.2016.054
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem Cell Transplantation for Adult Patients With Fanconi Anemia.

Abstract: Background and objectivesFanconi anemia (FA) is a rare genetic disorder caused by an impaired DNA repair mechanism which leads to an increased tendency toward malignancies and progressive bone marrow failure. The only curative management available for hematologic abnormalities in FA patients is hematopoietic stem cell transplantation (HSCT). This study aimed to report the results of HSCT in adult or adolescent FA patients.Patients and MethodsTwenty FA patients with ages of 16 or more who underwent HSCT between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In contrast, these patients are also at risk for excessive weight including obesity, in most cases, probably due to metabolic alterations, especially abnormalities in the glucose and insulin metabolism as was observed in studies performed with humans and animals. 3 , 18 Excessive weight was found in at least 10% of the members of all groups analyzed in this study, with obesity only found in children and adolescents. Rose et al identified similar results on assessing an adult population, in which 11% were overweight.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In contrast, these patients are also at risk for excessive weight including obesity, in most cases, probably due to metabolic alterations, especially abnormalities in the glucose and insulin metabolism as was observed in studies performed with humans and animals. 3 , 18 Excessive weight was found in at least 10% of the members of all groups analyzed in this study, with obesity only found in children and adolescents. Rose et al identified similar results on assessing an adult population, in which 11% were overweight.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, an analysis of the ROC curve, even considering only the potentially healthier patients since they were evaluated more than six months after the transplant, showed that more than one and a half years would be necessary to reach normal weight parameters according to their BMI. Studies indicate that from 22% to 38% of FA patients are underweight 3 , 16 ; this may occur due to anatomical alterations of the gastrointestinal tract, chronic inflammation, infection, or as consequences of pharmacological treatment, resulting in early satiety, reflux, nausea, emesis, and diarrhea. 17 This study found similar results: 20% of non-transplanted children and adolescents had decreased BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations